Poor Information Quality of Abdominal Aortic Aneurysm Videos on Chinese Social Media: A Cross-Sectional Study. - Wang, Julin; Xie, Yang; Miao, Tianyu; Li, Yang; Zhao, Jichun; Huang, Bin (Inquiry (00469580), 2025)
Abdominal aortic aneurysm (AAA) is a severe vascular disease. Given the high dependency of Chinese users on domestic social media platforms, this study aimed to evaluate the content completeness and information quality of AAA related videos on China's dominant social media. We searched for the keyword "abdominal aortic aneurysm" on the Chinese social media TikTok and Bilibili. The top 100 search results for each platform were collected based on the default sorting. The video content was evaluated for completeness and information quality using abdominal aortic aneurysm specific score (AAASS), modified DISCERN tool (mDISCERN), and Global Quality Scale (GQS). The study included 140 social media videos. Among all videos, median scores (IQR) for AAASS, mDISCERN, and GQS were 3.00 (2.00-4.00), 2.00 (1.00-3.00), and 3.00 (2.00-3.00). Analysis of correlations between video duration and engagement metrics revealed a weak positive correlation between "shares" and duration (r =.221, P =.009). Associations between engagement metrics and quality scales showed only "shares" correlated with GQS (r =.216, P =.011), while video duration demonstrated positive correlations with AAASS (r =.211, P =.012) and GQS (r =.234, P =.005). In various uploader identities, radiologists had significantly lower GQS scores than vascular surgeons, medical institutions, and cardiothoracic surgeons (P <.01). This study shows that videos about abdominal aortic aneurysm on Chinese social media exhibited poor content completeness and information quality. This highlights an urgent need for platforms to improve quality control algorithms and for medical professionals to be guided in producing more comprehensive, evidence-based content.